2020
DOI: 10.1021/acsami.0c03672
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering of NiO/NiCo2O4 Porous Nanofibers as Efficient Bifunctional Catalysts for Rechargeable Zinc–Air Batteries

Abstract: To meet the crucial demand of regenerative Zn–air (ZA) batteries, low cost, highly efficient, and durable electrocatalysts for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are needed to replace the noble metal. Herein, porous NiO/NiCo2O4 nanofibers with superior electrocatalytic performance are synthesized by a facile electrospinning strategy with precursor transition metal salts in nonstoichiometric ratio, which confers the heterostructured NiO/NiCo2O4 with abundant interface-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Meanwhile, metal oxide has a better affinity binding effect for oxygen, which can exhibit the character of excellent stability under alkaline or acidic conditions, and further contribute a synergetic effect with the carbon electrospun nanofibers. [ 111–121 ] Recently, the Co 3 O 4 hollow particles (Co 3 O 4− x HoNPs) supported on hierarchically porous N‐doped carbon structure (HPNCS) are prepared by the growth of leaf‐like Co‐ZIFs and subsequent heating treatment of electrospun nanofibers ( Figure a). [ 122 ] The carbon flake structure can be distributed on carbon nanofibers, which have a large surface area and rich oxygen vacancy defects (Figure 10b).…”
Section: Electrospinning In Zabsmentioning
confidence: 99%
“…Meanwhile, metal oxide has a better affinity binding effect for oxygen, which can exhibit the character of excellent stability under alkaline or acidic conditions, and further contribute a synergetic effect with the carbon electrospun nanofibers. [ 111–121 ] Recently, the Co 3 O 4 hollow particles (Co 3 O 4− x HoNPs) supported on hierarchically porous N‐doped carbon structure (HPNCS) are prepared by the growth of leaf‐like Co‐ZIFs and subsequent heating treatment of electrospun nanofibers ( Figure a). [ 122 ] The carbon flake structure can be distributed on carbon nanofibers, which have a large surface area and rich oxygen vacancy defects (Figure 10b).…”
Section: Electrospinning In Zabsmentioning
confidence: 99%
“…Zhan et al synthesized NiO/NiCo 2 O 4 heterogeneous fiber structure electrocatalyst with good coupling interface by electrospinning. 11 Further, the nonwoven polymer fiber materials prepared by electrospinning have been applied in practice. For example, they are beneficial to utilize as a gas mask to protect people's respiratory system, and can also be used in the air purification system of the operating room.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Gao and Xue groups fabricated the NiO/NiCo 2 O 4 porous nanofibers, and such nanofibers exhibited efficient and durable OER performance. [19] In recent study, Zheng et al prepared an NiSe 2 / CoSe 2 heterostructure with dense interfaces, which showed incredible OER activity, manifested by an extremely low overpotential of 286 mV at 10 mA cm À 2 in 1 M KOH. [20] Heteroatom doping, [21] defect engineering, [22] single atom/active site construction, [23] and other strategies have been employed as available means to optimize the electrocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…discovered that, graphitic carbon nitride/carbon nanotubes supported NiCo 2 S 4 showed superior OER performance to the benchmark RuO 2 catalyst, featuring low overpotential, high efficiency and robust stability [18] . Gao and Xue groups fabricated the NiO/NiCo 2 O 4 porous nanofibers, and such nanofibers exhibited efficient and durable OER performance [19] . In recent study, Zheng et al.…”
Section: Introductionmentioning
confidence: 99%